2014
DOI: 10.1016/j.micres.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Construction of individual, fused, and co-expressed proteins of endoglucanase and β-glucosidase for hydrolyzing sugarcane bagasse

Abstract: At least a combination of endoglucanase (EglII) and β-glucosidase (BglZ) is required for hydrolyzing crystalline cellulose. To understand the catalytic efficiency of combination enzymes for converting biomass to sugars, EglII and BglZ were constructed in the form of individual, fused as well as co-expression proteins, and their activities for hydrolyzing sugarcane bagasse were evaluated. The genes, eglII isolated from Bacillus amyloliquefaciens PSM3.1 earlier and bglZ from B. amyloliquefaciens ABBD, were expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…and Co-expression of endoglucanase and beta-glucosidase were successfully carried out in E. coli [36]. Several other reports indicating fusion and co-expression of proteins belong to endoglucanase and β-glucosidase for hydrolyzing sugarcane bagasse [38]. Thus chitinase and protease can be successfully fused and expressed in E.coli without changing their catalytic activities, properties, and kinetics.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…and Co-expression of endoglucanase and beta-glucosidase were successfully carried out in E. coli [36]. Several other reports indicating fusion and co-expression of proteins belong to endoglucanase and β-glucosidase for hydrolyzing sugarcane bagasse [38]. Thus chitinase and protease can be successfully fused and expressed in E.coli without changing their catalytic activities, properties, and kinetics.…”
Section: Plos Onementioning
confidence: 99%
“…The co-expression strategies have the limitation of low transformation efficiency and inconvenient screening during co-expression. Constructing a bifunctional/trifunctional gene could be an effective approach [34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid this problem, constructing a trifunctional cellulase with a single gene could be an effective solution. Many successful studies have been performed on developing the bifunctional cellulase with fusion expression of two different catalytic domains, including endoglucanase catalytic domain fused with β-glucosidase catalytic domain [ 14 , 22 ], exoglucanase catalytic domain fused with β-glucosidase catalytic domain [ 15 ], exoglucanase catalytic domain fused with endoglucanase catalytic domain [ 25 ]. However, it has not been reported of an active trifunctional cellulase with three different catalytic domains.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, fusion expression strategy, a biotechnology alternative to co-expression, have also been used to express multiple enzymes simultaneously with many advantages including the convenient manipulations of cloning and transforming, the high level of soluble expression, cost-effective purification, and upgraded catalytic capabilities [ 21 ]. In addition, it has been confirmed that all individual, fused, and co-expressed endoglucanases and β-glucosidases play a role in hydrolyzing sugarcane bagasse [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in order to obtain a cellulase consortium containing different cellulolytic activities, fusion expression has been applied for the synthesis of bifunctional enzymes that enable cellulose hydrolysis [ 20 , 21 ]. It has been proven that individually expressed, fused, and co-expressed endoglucanases and β-glucosidases can promote the hydrolysis of sugarcane bagasse [ 22 ].…”
Section: Introductionmentioning
confidence: 99%